Developing National Cancer Registration in Developing Countries – Case Study of the Nigerian National System of Cancer Registries - Jedy-Agba, Elima E.; Oga, Emmanuel A.; Odutola, Michael; Abdullahi, Yusuf M.; Popoola, Abiodun; Achara, Peter; Afolayan, Enoch; Banjo, Adekunbiola Aina Fehintola; Ekanem, Ima-Obong; Erinomo, Olagoke; Ezeome, Emmanuel; Igbinoba, Festus; et al. (Frontiers in Public Health, 2015)
The epidemiological transition in sub-Saharan Africa (SSA) has given rise to a concomitant increase in the incidence of non-communicable diseases including cancers. Worldwide, cancer registries have been shown to be critical for the determination of cancer burden, conduct of research, and in the planning and implementation of cancer control measures. Cancer registration though vital is often neglected in SSA owing to competing demands for resources for healthcare. We report the implementation of a system for representative nation-wide cancer registration in Nigeria – the Nigerian National System of Cancer Registries (NSCR). The NSCR coordinates the activities of cancer registries in Nigeria, strengthens existing registries, establishes new registries, complies and analyses data, and makes these freely available to researchers and policy makers. We highlight the key challenges encountered in implementing this strategy and how they were overcome. This report serves as a guide for other low- and middle-income countries (LMIC) wishing to expand cancer registration coverage in their countries and highlights the training, mentoring, scientific and logistic support, and advocacy that are crucial to sustaining cancer registration programs in LMIC.